2011
DOI: 10.1088/1674-1056/20/9/097105
|View full text |Cite
|
Sign up to set email alerts
|

A time-dependent density functional theory investigation of plasmon resonances of linear Au atomic chains

Abstract: We report theoretical studies on the plasmon resonances in linear Au atomic chains by using ab initio timedependent density functional theory. The dipole responses are investigated each as a function of chain length. They converge into a single resonance in the longitudinal mode but split into two transverse modes. As the chain length increases, the longitudinal plasmon mode is redshifted in energy while the transverse modes shift in the opposite direction (blueshifts). In addition, the energy gap between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…To date, many study results have indicated that quantum chemical method, especially the density-functional theory (DFT), is a powerful method of predicting the geometry and harmonic vibrations of organic compounds. [17][18][19][20][21][22][23][24][25] The DFT is a useful method for investigating large molecules. For example, Jursic and Martin, [17] and Jursic [18] produced the reliable BDEs for H-O, O-O, and C-N bonds by hybrid B3LYP method and non-local BLYP method.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many study results have indicated that quantum chemical method, especially the density-functional theory (DFT), is a powerful method of predicting the geometry and harmonic vibrations of organic compounds. [17][18][19][20][21][22][23][24][25] The DFT is a useful method for investigating large molecules. For example, Jursic and Martin, [17] and Jursic [18] produced the reliable BDEs for H-O, O-O, and C-N bonds by hybrid B3LYP method and non-local BLYP method.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous works, it has been successfully used in predicting the absorption and plasmon resonances of nanostructures. [32][33][34][35][36] In the calculation, the inner shell electrons are treated by the Troullier-Martins norm-conserving pseudopotentials, [37] and the exchange and correlation interaction is included within the local-density approximation (LDA). [38] The linear response can be obtained by propagating the system with time-dependent Kohn-Sham equations under an impulse perturbation with a damping parameter of 0.15 a.u.…”
Section: Methods Of Calculationsmentioning
confidence: 99%
“…Theoretically, Kümmel and co-workers showed in 2001 that the excitations can be considered as collective plasmons in few-atom metal clusters . TDDFT calculations have demonstrated the collective excitations in various atomic metal chains of more than 10 atoms. Johnson et al and Picinni et al examined the intense absorption peak in the absorption spectrum for Au and Ag nanochain/nanorods systems and suggested that the peak differs from single-particle transitions and can be identified as plasmon excitation. , Therefore, it is reasonable to use a nanowire to model the plasmon-induced process.…”
Section: Introductionmentioning
confidence: 99%